(untitled) (Análisis Económico, 2023)
Using Mexican data from January 2002 to August 2017, this paper estimates a SVAR recursively identified through a model that satisfies New Keynesian core assumptions. Two key contributions are 1) evince that expected inflation is formed according to static expectations hypothesis; 2) suggest nominal rigidities presence, which reinforces the reasons to assess the Mexican economy through the New Keynesian Model; moreover, impulse response functions indicate: expected inflation influencing observed inflation; interest rate endogenously reacting to output and inflation, as to expected inflation decreases; higher interest rate entailing lower inflation and output. JEL Classification: E13; C32; C50; O11.